The rip current hazard in Costa Rica - Arozarena, Isabel (2015)
Deaths from rip currents are a major hazard on global beaches, but few data are available at a national scale to support the development of appropriate intervention programs. Analysis of data from the Judicial Investigation Organization of Costa Rica indicates that drowning is the leading cause of violent death in the country, with 1,391 drownings between 2001 and 2012. Approximately 590 of those drownings occurred in a marine environment and are listed as being the result of rip currents. A majority (64 %) of the drownings attributed to rip currents involved victims from Costa Rica and tended to involve young single male students at beaches within a relatively short drive from San Jose on weekends and on national holidays. In comparison, the majority of foreign drowning victims were older males from the USA and Nicaragua with no statistically significant variation in the number of those drownings by day of the week. Predicted wave forcing and measured sediment characteristics suggest that the majority of drownings are associated with a transverse bar and rip (TBR) morphology with quasi-steady rip channels close to the beach. The interannual variation in both local and foreign drownings exhibits a statistically significant dependency on the variation in wave height with the Pacific-North American (PNA) Oscillation. Specifically, drownings peak during the negative phase of the PNA when wave heights are significantly smaller, which may reflect a tendency for beach users to enter calm water when the beach tends to have a TBR morphology. Further study is required to characterize the rip hazard at the most popular beaches on the Pacific and Caribbean coasts and to determine the level of rip knowledge by both local and foreign beach users.